DAMPAK PELATIHAN BIMBINGAN DAN KONSELING TERHADAP PENINGKATAN KEMAMPUAN GURU DALAM PENGEMBANGAN LAYANAN DI SEKOLAH DASAR - A.Fauzi, Ikka Kartika (Pendidikan Dasar, 2009)
Abstract: The success of training is often seen from the output aspect. The criteria for this  success is on the participants’  ability in completing the training with the over-average achievement. Achieving  the competency change, moreover performance, an output aspect is merely a preliminary goal, while the main goal is outcome, impact. So, it can be said that the ability in achieving the final goal is a form of success.